Learning from the unexpected in life and DNA self-assembly - Heemstra, Jennifer M. (Beilstein Journal of Organic Chemistry, 2015)
The greatest lessons in life and science often arise from the unexpected. Thus, rather than viewing these experiences as hindering our progress, they should be embraced and appreciated for their ability to lead to new discoveries. In this perspective, I will discuss the unexpected events that have shaped my career path and the early stages of my independent research program.
Keywords: aptamers; DNA self-assembly; nucleic acids

Are you always this enthusiastic? - Heemstra, J. M. (2015)

Do Babies Matter? Gender and Family in the Ivory Tower - Mason, M. A.; Wolfinger, N. H.; Goulden, M. (Rutgers University Press, 2013)

(untitled) - Sharma, A. K.; Plant, J. J.; Rangel, A. E.; Khoe, K. N.; Anamisis, A. J.; Hollien, J.; Heemstra, J. M. (ACS Chem. Biol., 2014)

(untitled) - Feagin, T. A.; Olsen, D. P. V.; Headman, Z. C.; Heemstra, J. M. (J. Am. Chem. Soc., 2015)

(untitled) - Huizenga, D. E.; Szostak, J. W. (Biochemistry, 1995)

(untitled) - Stojanovic, M. N.; de Prada, P.; Landry, D. W. (J. Am. Chem. Soc., 2000)

(untitled) - Liu, J.; Cao, Z.; Lu, Y. (Chem. Rev., 2009)

(untitled) - Zhang, J.; Wang, L.; Pan, D.; Song, S.; Boey, F. Y. C.; Zhang, H.; Fan, C. (Small, 2008)

(untitled) - Sletten, E. M.; Bertozzi, C. R. (Angew. Chem., Int. Ed., 2009)

(untitled) - Schildkraut, C.; Lifson, S. (Biopolymers, 1965)

(untitled) - Sharma, A. K.; Heemstra, J. M. (J. Am. Chem. Soc., 2011)

(untitled) - Spiropulos, N. G.; Heemstra, J. M. (Artif. DNA PNA XNA, 2012)

(untitled) - Sharma, A. K.; Kent, A. D.; Heemstra, J. M. (Anal. Chem., 2012)

(untitled) - McKeague, M.; DeRosa, M. C. (J. Nucleic Acids, 2012)

(untitled) - Yang, K.-A.; Pei, R.; Stefanovic, D.; Stojanovic, M. N. (J. Am. Chem. Soc., 2012)

(untitled) - Kent, A. D.; Spiropulos, N. G.; Heemstra, J. M. (Anal. Chem., 2013)

(untitled) - Reetz, M. T.; Wilensek, S.; Zha, D.; Jaeger, K.-E. (Angew. Chem., Int. Ed., 2001)

A Practical Guide to Assay Development and High-Throughput Screening in Drug Discovery - Chen, T. (CRC Press, 2010)

(untitled) - Klußmann, S.; Nolte, A.; Bald, R.; Erdmann, V. A.; Fürste, J. P. (Nat. Biotechnol., 1996)

(untitled) - Nutiu, R.; Li, Y. (J. Am. Chem. Soc., 2003)

(untitled) - Zhu, Z.; Schmidt, T.; Mahrous, M.; Guieu, V.; Perrier, S.; Ravelet, C.; Peyrin, E. (Anal. Chim. Acta, 2011)